Sunny Blume, Mrs Thomas Stevenson, and Donna Stinecipher - Unknown:::Creator::::::::::::
Photograph is of Sunny Blum, Mrs. Thomas Stevenson and Donna Stinecipher at the 1962 YWCA World Fellowship Benefit. The two ladies on either end are dressed in costume. The woman on the left is dressed as Auntie Mame.